Augmentation of Air Cathode Microbial Fuel Cell Performance using Wild Type Klebsiella Variicola - Islam, M. Amirul; Karim, Ahasanul; Chee, Wai Woon; Ethiraj, Baranitharan; Cheng, C. K.; Yousuf, Abu; Khan, Maksudur R. (Royal Society of Chemistry, 2017)
In the present work, simultaneous power generation and wastewater treatment in the single chamber air cathode microbial fuel cell (MFC) have been enhanced by introducing wild-type Klebsiella variicola (K. variicola) as an efficient inoculum for the anode operated with palm oil mill effluent (POME). K. variicola was isolated from municipal wastewater (MWW) and identified using BIOLOG gene III analysis, PCR and sequencing. The performance of K. variicola in MFC was evaluated by polarization curve measurement, electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) analysis. The MFC with K. variicola achieved a maximum power density of about 1.7 W m−3 which is comparatively higher than most widely used anaerobic sludge (215 mW m−3) as an inoculum whereas COD removal efficiency is (43%) lower than anaerobic sludge (74%). Moreover, K. variicola has the ability to produce electron shuttles and to form biofilms on the electrode surface which helps to significantly reduce the anode charge transfer (Rct) resistance compared to the anaerobic sludge. These results revealed the potential of K. variicola to be used in MFC.